2016
DOI: 10.1007/s40948-016-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength characteristics of shotcrete–rock interface for a tunnel driven in high rock temperature environment

Abstract: The shear behavior of shotcrete-rock interface same as the bond behavior plays a significant role on shotcrete behaviour in a tunnel. The shear strength of shotcrete-rock interface is noticeably affected by high temperature in high rock temperature tunnels. However, there are limited number of studies dedicated to investigate behaviour of shotcrete-rock interface in high temperatures. Therefore, a series of direct shear tests was performed, under the normal stress of 0.5, 1.0 or 1.5 MPa, to investigate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This paper is based on a preliminary study aimed to investigate the distribution of the temperature field and the application of a prediction model in the high geothermal tunnel. It has been proven that the results of the model calculation are consistent with the field experiment data and previous results from the numerical simulation [37,38], revealing that the proposed temperature prediction model can better meet the computational requirements for actual engineering tasks. However, many more factors also have a great impact on the distribution of the temperature field, such as lithology and size of the cross-section, especially the cooling measures.…”
Section: Discussionsupporting
confidence: 73%
“…This paper is based on a preliminary study aimed to investigate the distribution of the temperature field and the application of a prediction model in the high geothermal tunnel. It has been proven that the results of the model calculation are consistent with the field experiment data and previous results from the numerical simulation [37,38], revealing that the proposed temperature prediction model can better meet the computational requirements for actual engineering tasks. However, many more factors also have a great impact on the distribution of the temperature field, such as lithology and size of the cross-section, especially the cooling measures.…”
Section: Discussionsupporting
confidence: 73%
“…The peak strength of marbles under uniaxial compression conditions exhibits a first decreasing, then increasing and decreasing again trend. When T ≤ 300 °C, peak strength slowly decreases from 60.61 MPa to 29.96 MPa at a rate of 0.11 MPa/ °C. In the range of 300 ~600 °C, peak strength slowly increases from 29.96 MPa to 115.52 MPa at a rate of 0.29 MPa/ °C with the increment of T. As T rises from 600 °C to 800 °C, peak strength decreases again from 115.52 MPa to 34.24 MPa at a rate of 0.41 MPa/ °C.…”
Section: Mechanical Behaviors Under Uniaxial Compressionmentioning
confidence: 99%
“…The physical and mechanical characteristics of rocks after high-temperature exposure have been diffusely studied [20][21][22][23][24][25][26][27][28][29]. For red sandstones, a fracture evolution process was conducted by Yang et al [30] on a specimen containing a single fissure and two parallel cracks under uniaxial compression, which was heated by thermal treatment from 25 °C to 900 °C.…”
Section: Introductionmentioning
confidence: 99%
“…rough the abovementioned high-temperature disaster cases, it can be found that if the high ground temperature problem occurs in the tunnel project, the construction environment, building materials, machinery and equipment, and the operation of the tunnel after completion will be inevitably affected ( Figure 2). Globally, the adverse effects of geothermal high temperature on tunnel construction can be summarized as the following aspects [2,17,[23][24][25]:…”
Section: Causes and Effects Of Terrestrial Heatmentioning
confidence: 99%
“…On the contrary, in an environment with a certain temperature and low humidity, the moisture inside the concrete will be lost due to the hydration reaction, and the hydrated calcium silicate gel supplements the capillary water on the concrete surface, which reduces the cohesive force of the gel and weakens the cohesion of the rock-concrete interface to some extent. On further research on shotcrete-torock adhesion strength, Tong et al [24] believed that, in high-temperature tunnels, temperature and humidity will indirectly affect the speed and extent of concrete hydration, making rock-concrete interface failure; at this time, the degree of adhesion of the shotcrete-to-rock depends on the roughness of the interface, the rock-concrete interface is ineffective, and the degree of cohesion of the rock-concrete interface depends on the roughness of the interface (Figure 7). In order to better study the influence of temperature and humidity on the shotcrete-to-rock adhesion strength, it is generally necessary to clean the surface of the rock mass before the experiment to reduce the influence of the interface roughness [10, 36, 45].…”
Section: Effect Of Temperature and Humidity On Adhesion Strength Of Smentioning
confidence: 99%